Why Did Kath, Mary and Kim Get So Little Education (and Is There Hope for Their Children)? - Liz Gordon (New Zealand Journal of Teachers' Work)
This paper seeks to understand the reasons why there is such a strong relationship between poverty and poor child educational outcomes. It reports preliminary findings of in-depth interviews with three women who have spent most of the past five years on the DPB and live in the poorest part of Christchurch. The focus of this paper is on these women’s own education and the education of their children. All three left school before or at the minimum leaving age with no qualifications. With a range of unresolved familial issues, these young women were clearly at risk of negative life outcomes, but they reported no intervention to keep them in education. All had children at a comparatively young age. All have aspirations for their children beyond their own achievements, and see education as the key to this. However, they have few family resources to assist in the achievement of these goals. In particular, the women have quite low self-esteem which is a barrier to their aspirations. The conclusion raises some possibilities about how practitioners might intervene to prevent the children suffering the same fate as their parents.